Pretibial dystrophic epidermolysis bullosa pruriginosa: A rare case report in a child with low intelligent quotient - B Vijaya; S R Narahari; Pallavi Deka; G V Manjunath (Wolters Kluwer Medknow Publications, 2016)
Dystrophic epidermolysis bullosa (DEB), a rare form of EB, is characterized by defects in Type VII collagen which is encoded by COL7A1 gene located on chromosome 3p21. A 12-year-old female with low intelligent quotient presented with intensely pruritic multiple violaceous papules which were coalescent at areas on both the shins. Histopathological examination showed epidermis displaying focal thinning. A subepidermal cleft was seen beneath the basement membrane zone. The dermis showed a linear array of keratinous cysts with intervening diffuse lymphohistiocytic infiltrate. Features were suggestive of pretibial DEB. Since it was associated with intense itching, the lesion was termed as pretibial DEB pruriginosa which has combined elements of exclusive pretibial lesions and intense itching. An appropriate clinical history and increased awareness of histopathological features will enable earlier diagnosis and suitable management.